Influences of early child nutritional status and home learning environment on child development in Vietnam - Nguyen, Phuong Hong; DiGirolamo, Ann M.; Gonzalez-Casanova, Ines; Young, Melissa F.; Kim, Nicole; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2018)
Early childhood development plays a key role in a child's future health, educational success, and economic status. However, suboptimal early development remains a global challenge. This study examines the influences of quality of the home learning environment (HOME) and child stunting in the first year of life on child development. We used data collected from a randomized controlled trial of preconceptional micronutrient supplementation in Vietnam (n = 1,458). The Bayley Scales of Infant Development‐III were used to assess cognition, language, and motor development domains at 2 years. At 1 year, 14% of children were stunted, and 15%, 58%, and 28% of children lived in poor, medium, and high HOME environments, respectively. In multivariate generalized linear regression models, living in a high HOME environment was significantly associated with higher scores (0.10 to 0.13SD) in each of the developmental domains. Stunted children scored significantly lower for cognitive, language, and motor development (−0.11 to −0.18), compared to nonstunted children. The negative associations between stunting on development were modified by HOME; the associations were strong among children living in homes with a poor learning environment whereas they were nonsignificant for those living in high‐quality learning environments. In conclusion, child stunting the first year of life was negatively associated with child development at 2 years among children in Vietnam, but a high‐quality HOME appeared to attenuate these associations. Early interventions aimed at improving early child growth as well as providing a stimulating home environment are critical to ensure optimal child development.